2012
DOI: 10.3892/ol.2012.804
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect and immune response induced by local hyperthermia in B16 murine melanoma: Effect of thermal dose

Abstract: Abstract. This study aimed at investigating the antitumor effect and immune response induced by local high-temperature hyperthermia at different thermal doses in B16 murine melanoma. The screened optimal thermal dose (50˚C, 15 min) which was demonstrated to be the most effective in immune response activation was applied to the treatment of lung metastasis. The optimal thermal dose was determined by evaluating the tumor volume change, survival period of tumorbearing mice, and immune indices including interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…In contrast, tumors exposed to thermal ablation showed significant cellular damage characterized by regions of thermonecrosis, corrupt extracellular matrix, damaged or enlarged cell nuclei, and coagulation (Figure 3F). These are some of the common observations in photothermal ablative therapies 40 . As further evidence that MHT caused no vascular hindrance by vascular damage and shutdown, dye flow was observed 24 h after treatment (Supplementary, Figure S3); unlike previous studies in which vascular occlusion was observed as early as 24 h after hyperthermia treatment 23 .…”
Section: Resultsmentioning
confidence: 68%
“…In contrast, tumors exposed to thermal ablation showed significant cellular damage characterized by regions of thermonecrosis, corrupt extracellular matrix, damaged or enlarged cell nuclei, and coagulation (Figure 3F). These are some of the common observations in photothermal ablative therapies 40 . As further evidence that MHT caused no vascular hindrance by vascular damage and shutdown, dye flow was observed 24 h after treatment (Supplementary, Figure S3); unlike previous studies in which vascular occlusion was observed as early as 24 h after hyperthermia treatment 23 .…”
Section: Resultsmentioning
confidence: 68%
“…The resulting tumor damage led to the release of the DAMP signaling molecules hsp70, HMGB1, and ATP. Although others reported that higher temperatures completely eradicated the primary melanoma tumors [30], it was also shown that although higher temperature (i.e., above 43 °C) was more effective in primary tumor destruction, it completely abrogated the resistance against secondary tumors, most probably by inducing necrotic cell death, which was not effective in mounting anti-tumor immunity [31]. Next, we dissected the molecular pathways leading to tumor regression induced by mEHT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tumor growth inhibition efficacy of the BLs and HIFU group was better than that of the HIFU alone group (p<0.05). It has been reported that local hightemperature hyperthermia (50-55°C) enhanced the indices of the T helper 1 (Th1) immune response, such as interleukin-2 (IL-2), interferon-gamma (IFN-γ), and tumor necrosis factoralpha (TNF-α) 8) ; therefore, it could be suggested that the antitumor effect of BLs and HIFU exposure was due to the ablation effect and immune response.…”
Section: Resultsmentioning
confidence: 99%